Diabetes Mellitus Versus Hypertension—Does Disease Affect Pharmacological Adherence? - Jankowska-Polańska, Beata; Karniej, Piotr; Polański, Jacek; Seń, Mariola; Świątoniowska-Lonc, Natalia; Grochans, Elżbieta (Frontiers in Pharmacology, 2020)
The aim of the study was to answer the questions whether a chronic disease can have a significant impact on the level of adherence and whether there are differences in adherence-related predictors depending on the chronic disease. The study included 1571 patients (mean age 64.7±11.3) with chronic diseases (1030 diabetes mellitus (DM) type 2 and 541 hypertension (HA)). Adherence was assessed using the Adherence Refills Medication Scale (ARMS). The average adherence score for the whole group was 18.9. 55% of patients had a low level of adherence. A comparison between DM and HA shows a statistically significant difference and a higher level of adherence with pharmacological recommendations in the group of patients with type 2 DM (17.5±12.0 vs 19.2±8.0). In the single factors analysis, HA diagnosis had a statistically significant negative effect on adherence (β=0.92, p≤0.001). In simple linear regression analysis, independent of chronic disease, a higher level of adherence was observed among women (β=-0.40, p=0.015), people with secondary education (β=-1.26, p≤0.001) and inactive patients (β=-0.48; p=0.005). However, place of residence - countryside (β =0.35, p=0.044) and higher education (β=0.90, p≤0.001) had a negative influence on the level of adherence. In multiple linear regression analysis HA (B=0.99; p≤0.001), female gender (B=-0.47; p=0.003) and secondary education (B=-1.16; p≤0.001) were important independent determinants of adherence. (1) Hypertension is an independent, statistically significant predictor that reduces the adherence level. (2) Female gender and higher education are the most important determinants improving adherence to pharmacological therapy. (3) There is a different pattern of predictors of adherence among patients: Occupational activity plays an important role in DM, while education plays a role in HA.